2020
DOI: 10.1186/s12284-020-00426-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Early Defenses in Rice against Fusarium fujikuroi

Abstract: Background Bakanae is a seedborne disease caused by Fusarium fujikuroi. Rice seedlings emerging from infected seeds can show diverse symptoms such as elongated and slender stem and leaves, pale coloring, a large leaf angle, stunted growth and even death. Little is known about rice defense mechanisms at early stages of disease development. Results This study focused on investigating early defenses against F. fujikuroi in a susceptible cultivar, Zerawchanica karatals (ZK), and a resistant cultivar, Tainung 67 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 118 publications
1
4
1
Order By: Relevance
“…It was inferred that invasion by Sporisorium destruens increased the JA content in the leaves of diseased broomcorn millet to resist Sporisorium destruens invasion. However, Cheng's research results showed that the genes associated with the JA biosynthetic process were up-regulated in the resistant cultivar, Selenio, and down-regulated in the susceptible Dorella cultivar [32], which was contrary to our result. Research on the role of JA in the interaction between broomcorn millet and smut needs further investigation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It was inferred that invasion by Sporisorium destruens increased the JA content in the leaves of diseased broomcorn millet to resist Sporisorium destruens invasion. However, Cheng's research results showed that the genes associated with the JA biosynthetic process were up-regulated in the resistant cultivar, Selenio, and down-regulated in the susceptible Dorella cultivar [32], which was contrary to our result. Research on the role of JA in the interaction between broomcorn millet and smut needs further investigation.…”
Section: Discussioncontrasting
confidence: 99%
“…Sequencing analysis identified 514 and 5452 DEGs in the resistant and susceptible cultivars, respectively. This result was consistent with the study by Cheng et al [32], in which inoculation of Tainung 67 (resistant rice cultivar) and Zerawchanica karatals (susceptible rice cultivar) with Fusarium fujikuroi resulted in the appearance of 118 and 169 DEGs, respectively. Hence, susceptible varieties tend to activate gene expression in response to stress.…”
Section: Discussionsupporting
confidence: 93%
“…JA-dependent defense responses are important factors in resistance to F. fujikuroi in rice [ 14 , 16 ]. To determine whether OsWRKY114 is also involved in JA responses, we analyzed the expression levels of various JA-related genes in OsWRKY114 OX .…”
Section: Resultsmentioning
confidence: 99%
“…High-performance liquid chromatography-mass spectrometry and comparative transcriptome profiling showed that increasing GA and decreasing JA levels in infected plants are important for plant susceptibility to F. fujikuroi [ 14 , 15 ]. Transcriptome analysis revealed that the expression levels of JAZ genes decrease during the early stages of F. fujikuroi infection and that JA-dependent immunity is crucial for the resistance of rice to F. fujikuroi [ 16 ]. However, the signaling components and regulatory mechanisms of GA and JA signaling involved in rice– F. fujikuroi interactions are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have aimed to better understand the dynamics of key genes and regulatory mechanisms in rice associated with morphology [ 22 ], physiology [ 23 ], abiotic and biotic stress mechanisms [ 24 , 25 , 26 ]. Transcriptional control of nutrients during grain filling in rice has been studied by designing a GeneChip microarray covering half of the rice genome to understand the effect of genes participating in nutrient partitioning on starch quality [ 27 ].…”
Section: Introductionmentioning
confidence: 99%